(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the Jadidism movement, analyzing the historical works of the Khiva Jadids and the pedagogical and spiritual significance of teaching these works. Information is provided on the opportunities offered by the works of the Khiva Jadids for the younger generation to understand their national identity, develop moral virtues, and cultivate independent thinking skills.